Análisis de los decretos de estado de excepción en el Ecuador para combatir la delincuencia en el periodo 2021-2023 - Auz Flores, Sara Cristina (2024)
This research addresses the effectiveness of state of emergency decrees in Ecuador during the period 2021-2023, a key government strategy to combat rising crime in a context of high crime rates globally and regionally. Using a socio-legal approach, crime statistics and the specific measures implemented in each decree are analyzed in detail, with a particular emphasis on public security. Specific research objectives include determining trends and changes in crime rates in Ecuador, analyzing the measures adopted in each state of exception, and evaluating their effectiveness in reducing crime. A comparative approach is employed to analyze crime rates before, during and after the implementation of the decrees, providing a comprehensive view of the impact of these policies on security and social welfare, these results indicate a mixed effectiveness of the states of exception. Some decrees succeeded in decreasing crime in specific areas, while others showed an increase or a displacement of crime to other regions. These trends underscore the complexity of the crime situation in Ecuador and the need for integrated and adaptive strategies to effectively address crime in the country, the analysis contributes to the understanding of the dynamics of crime in Ecuador and the effectiveness of government measures. It offers valuable insights for future security policies and crime prevention strategies, highlighting the importance of an integrated approach that combines security measures with social and economic development initiatives.